The response of citrus plants to the broad mite Polyphagotarsonemus latus (Banks) (Acari: Tarsonemidae). (14th April 2021) - Cabedo‐López, Marc; Cruz‐Miralles, Joaquín; Peris, David; Ibáñez‐Gual, M. Victoria; Flors, Víctor; Jaques, Josep A.
Abstract : Polyphagotarsonemus latus (Banks) (Acari: Tarsonemidae) is a common polyphagous mite in tropical and subtropical areas and is considered as an important citrus pest. To understand the response of citrus to P. latus infestation, we have characterized the volatile profile and the molecular defence mechanisms of two citrus genotypes, namely sour orange ( Citrus aurantium ) and Cleopatra mandarin ( Citrus reshni ), to P. latus infestation. These two species are important rootstocks for the citrus industry and display differential resistance to Tetranychus urticae Koch (Acari: Tetranychidae), with sour orange showing elevated levels of constitutive and induced resistance associated with the jasmonic acid (JA) pathway compared with Cleopatra mandarin. P. latus infestation activated both the JA‐ and the salicylic acid‐dependent pathways in sour orange but not in Cleopatra mandarin. However, this differential activation resulted in the production of similar volatile blends (a mixture of green leaf volatiles and aromatic compounds). Contrary to T. urticae infestation, sour orange supported larger densities of P. latus than Cleopatra mandarin with similar injury levels. Therefore, sour orange may be more tolerant to P. latus than Cleopatra mandarin.